Peripheral venous pressure changes during exercise are associated with adverse Fontan outcomes. Issue 12 (30th October 2020) - Colman, Kathleen; Alsaied, Tarek; Lubert, Adam; Rossiter, Harry B; Mays, Wayne A; Powell, Adam W; Knecht, Sandra; Poe, Danielle; Ollberding, Nicholas; Gao, Zhiqian; Chin, Clifford; Veldtman, Gruschen R
Abstract : Objective: Elevated central venous pressure (CVP) plays an important role in the development of adverse Fontan outcomes. Peripheral venous pressure (PVP) has been validated as a surrogate for CVP in Fontan patients. We hypothesised that PVP in response to exercise will be associated with a greater prevalence of Fontan morbidity. Methods: Adult Fontan patients had cardiopulmonary exercise testing (CPET) with PVP monitoring in the upper extremity between 2015 and 2018. PVP at rest, during unloaded cycling and at peak exercise was compared between those with and without adverse Fontan outcomes including arrhythmia, unscheduled hospital admissions, heart failure requiring diuretics, need for reintervention and a composite outcome of the above morbidities, heart transplantation and death. Results: Forty-six patients with a mean age at CPET of 26.9±9.5 years. During exercise, PVP increased from 13.6±3.5 mm Hg at rest, to 16.5±3.9 mm Hg during unloaded cycling, to 23.0±5.5 mm Hg at peak exercise. Unloaded and peak PVP were more strongly associated than resting PVP with all adverse outcomes, except reintervention (composite outcome: resting PVP: OR 2.8, p=0.023; unloaded PVP: OR 6.1, p=0.001; peak PVP: OR 4.0, p<0.001). Cut-offs determined using ROC curve analysis had high specificity for the composite outcome (88% unloaded PVP ≥18 mm Hg; 89% peak PVP ≥25 mm Hg). Conclusion: Higher PVP at unloaded and peak exercise was strongly associated with a higher prevalence of adverse Fontan outcomes. Minimally invasive PVP monitoring during CPET may serve as a useful tool for risk stratifying individuals with a Fontan.